G191 THE MOZART EFFECT IN CHILDREN WITH EPILEPTIC EEGS. (4th June 2013) - Grylls, EK; Rudnay, J; Kinsky, M; Baggott, A; Wabnitz, C; McLellan, A
Abstract : Background: Listening to Mozart's Sonata for two pianos in D major (K448) has been found to enhance higher brain function such as spatial temporal reasoning and to have an anti-epileptic effect, demonstrated on EEGs (electroencephalograms). Aim: The aim of this study was to establish if the anti-epileptic effect of Mozart music on EEGs is present in children. Methods: Forty five children aged 0-18 with EEGs showing epileptiform activity were included in the study. They were selected opportunistically, from those attending for routine EEG analysis who had epileptic EEGs. Mozart's Sonata for two pianos in D major (K448) and an age-appropriate control music were used. Epileptic EEG activity was measured in five states, each lasting 5 minutes; before Mozart music (baseline), during Mozart music, after Mozart music/before control music, during control music and after control music. The results were analysed manually. Results: A significant reduction (p<0.0005) in the frequency of epileptic discharges was found during listening to the Mozart music compared to the baseline. No significant difference was found between the baseline and the other three states. No significant difference was found between during listening to the Mozart music and during listening to the control music. Conclusion: This study confirms an anti-epileptic effect of Mozart music on EEG activity in children, with a significant reduction in the frequency of epileptic discharges during listening to the Mozart music compared to the baseline, which was not present when listening to the control music. This study warrants further investigation into whether this effect could be achieved with other similarly structured music to Mozart. It opens doors to investigation into the long-term use as a therapy for epilepsy and to enhance understanding of epileptogenesis. Given the large proportion of children suffering from refractory epilepsy and the financial burden of epilepsy medication, a new therapy would be welcomed.